Bug safari: promoting ecological awareness in early childhood through nature-based learning - Kazım Biber; Caner Börekci (Institute of Advanced Engineering and Science, 2026)
This study examines the effectiveness of a nature-based educational program called bug safari, designed to enhance preschool children’s attitudes toward small creatures, particularly bugs, and to foster their ecological awareness. Developed within the framework of the Reggio Emilia approach, the program integrates multi-sensory and interdisciplinary learning methods, including observation, drama, storytelling, art activities, and parental involvement. The study was conducted in two preschool classrooms in Balıkesir, Türkiye. In the experimental group, bug safari activities were implemented once a week for six weeks, while the control group continued with the existing preschool curriculum. Data were collected using the 22-item bug awareness and ecological awareness questionnaire, developed by the researcher, and administered as both a pre-test and post-test. A mixed-design analysis of variance (ANOVA) revealed that the experimental group showed statistically significant improvements in bug awareness, understanding of the role of bugs in the ecosystem, and ecological consciousness, whereas no significant changes were observed in the control group. The findings indicated that nature-based programs involving direct experiences and active participation effectively promoted positive environmental attitudes and ecological awareness in early childhood. This study underscores the importance of integrating child centered, experiential, and nature-oriented approaches into preschool education to support cognitive, emotional, and behavioral development.